1991
DOI: 10.1111/j.1439-0507.1991.tb00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal action of Carica papaya latex: Isolation of fungal cell wall hydrolysing enzymes

Abstract: Summary. Carica papaya latex inhibits the growth of Candida albicans. Latex proteins appear to be responsible for this antifungal effect. The minimum protein concentration for producing a complete inhibition was estimated to be about 138 μg ml‐1. Exploration of different glycosidic activities shows that only α‐D‐mannosidase and N‐acetyl‐β‐D‐glucosaminidase were present in latex in important levels and they were partially purified. The two enzymes show a limited inhibitory effect on yeast growth, α‐D‐mannosida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…In the pharmaceutical industry, -mannosidases are currently used for treatment of mannosidosis, a congenital disorder of glycosides (CDG), by enzyme replacement therapy (Sun et al, 1999;Hirsch et al, 2003). Furthermore, it is suggested that -mannosidases be used synergistically with N-acetyl--hexosaminidase in the medical treatment of fungal diseases (Giordani et al, 1991). In vitro, -mannosidases are useful tools for enzymatic analysis of high mannose oligosaccharide structures (Maruyama et al, 1994;Misaki et al, 2003) and for oligosaccharide synthesis (Michalski et al, 1990;Athanasopoulos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the pharmaceutical industry, -mannosidases are currently used for treatment of mannosidosis, a congenital disorder of glycosides (CDG), by enzyme replacement therapy (Sun et al, 1999;Hirsch et al, 2003). Furthermore, it is suggested that -mannosidases be used synergistically with N-acetyl--hexosaminidase in the medical treatment of fungal diseases (Giordani et al, 1991). In vitro, -mannosidases are useful tools for enzymatic analysis of high mannose oligosaccharide structures (Maruyama et al, 1994;Misaki et al, 2003) and for oligosaccharide synthesis (Michalski et al, 1990;Athanasopoulos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hevea bransilensis latex shows antifungal activity against Trichosprum cutaneum and Cryptococcus neoformans [5]. It also exhibits a good activity against multiple drug resistant Staphylococcus aureus (NCTC 11994), Salmonella typhimurium (ATCC 1255) and Candida albicans (ATCC 10231) [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is a mixture of many pharmaceutically active substances which showed very high anti-bacterial [2], antiviral [3], antifungal [4] anti-protozoan activity. Latex from several plant species such as A. ochroleuca [2] Calotropis procera, Plumeria rubra, Carica candamarcensis, Euphorbia tirucalli (EtLP) [5], Erythrina variegata [6], Jatropha curcas, Hancornia speciosa Gomes (Apocynaceae) [7], C. procera [8], and Euphorbia lathyris [9] have shown very high antimicrobial activity. The leaves of J. curcas contain apigenin, vitexin and isovitexin, which along with other factors showed strong antibacterial activity against Staphylococcus aureus and Escherichia coli [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the patient reports it is cleared that it has a positive potential on hematological (Abdalla et al, 2013). Papaya juice also known as papaya milk has strong theraputical potential against fungal and bactericidal properties especially towards Candida albicans (Giordani and Siepai, 1991), hence, it is strongly useful to the protection from skin eczema caused by this fungus. Antiseptic quality of latex inhibits the growth of undesirable bacteria in human digestive system.…”
mentioning
confidence: 99%